TECHNOLOGY FOR DESIGNING STUDENTS CREATIVE ABILITIES - Asadovna, Polotova Qunduz (Journal of Learning on History and Social Sciences, 2025)
Objective: This study examines the enhancement of students' creative abilities in mother tongue education through pedagogical design and project-based methods. The goal is to integrate creativity into the learning process to improve educational quality and effectiveness. Method: A pedagogical experiment was conducted comparing creative, project-based learning with conventional explanatory teaching. The study involved systematic observation, task performance ratings, and feedback from both teachers and students. Quantitative and qualitative data were analyzed to ensure result validity. Results: The findings revealed that creatively designed lessons significantly increased students' motivation, engagement, and understanding. Students participated more actively in class, provided thoughtful responses, and demonstrated growth in applying knowledge and independent thinking. Teachers observed heightened eagerness and proactivity in students. Novelty: The study underscores the value of creative pedagogical design in mother tongue instruction, emphasizing its role in stimulating cognitive development and aligning educational practices with national standards, thereby contributing to sustained academic growth.